An Evaluation of Transport Related Government Web Sites in Sri Lanka - De Silva, A.P.U.; Gamage, Ruwan (Faculty of Graduate Studies, University of Kelaniya, 2015)
A Website is a mirror of the institute or the company. It has to play the main role of displaying vision, mission, tasks and everything of the institutes. So that, many government institutes use Websites to disseminate government information to the public. The main objective of the study was to find out whether the government Websites provided relevant information to the university community through their Websites. This study aim to find out solutions for five research questions, what information is required by university community, what sort of information is available in the government Websites, do the Websites provide relevant information to the university community, what kind of information services are provided by the government Websites, is there a better way to present government information through the Websites. In this study, both qualitative and quantitative methodologies were applied. Mainly this is a survey research. To collect primary data for the study, interviews, desk research and Website evaluation tools were used. 125 interviews were conducted among university staff and undergraduates to find out required information from the government Website. Desk research was conducted to collect existing information on the Websites. Sampled government institutes were evaluated using evaluation tools like WAVE, Google Page Speed and Hubspot Marketing Grader. After analyzing the data and evaluating Websites, it was realized that government institutes are unable to reach the expected level of the university community by providing online services and relevant information. There is a high demand for online services on government Websites. But a very few government Websites are provided online services for the users. Most of the government Websites were put on lower grade by the evaluation tools. In order to fill these discrepancies, some major moves are suggested to upgrade the rank of government Websites which are, following WCAG and proprietary accessibility guidelines, establishing formal web accessibility laws and guidelines, upgrading online services, training to web masters, recruiting a centralized post called web manager for all government institutes.
Keywords: Government Websites; Sri Lanka; Transport Related Government Websites; Websites Evaluation; Government Information; Sri Lanka Government